Breather Molecular Complexes in a Passively Mode‐Locked Fiber Laser. Issue 7 (9th June 2021) - Peng, Junsong; Zhao, Zihan; Boscolo, Sonia; Finot, Christophe; Sugavanam, Srikanth; Churkin, Dmitry V.; Zeng, Heping
Abstract: Breathing solitons are nonlinear waves in which the energy concentrates in a localized and oscillatory fashion. Similarly to stationary solitons, breathers in dissipative systems can form stable bound states displaying molecule‐like dynamics, which are frequently called breather molecules. So far, the experimental observation of optical breather molecules and the real‐time detection of their dynamics are limited to diatomic molecules, that is, bound states of only two breathers. In this work, the observation of different types of breather complexes in a mode‐locked fiber laser: multibreather molecules, and molecular complexes originating from the binding of two breather‐pair molecules or a breather pair molecule and a single breather is reported. The intermolecular temporal separation of the molecular complexes attains several hundreds of picoseconds, which is more than an order of magnitude larger than that of their stationary soliton counterparts and is a signature of long‐range interactions. Numerical simulations of the laser model support the experimental findings. Moreover, nonequilibrium dynamics of breathing solitons are also observed, including breather collisions and annihilation. This work opens the possibility of studying the dynamics of many‐body systems in which breathers are the elementary constituents. Abstract : Soliton molecules show striking dynamics that fuel the analogy with matter molecules, such as vibration and resonant excitation. Contrary to the significant progress made in the study of stationary soliton molecules, the existence of breathing soliton molecules is less explored. Here, different types of breather molecular complexes are demonstrated by tailoring the dispersive wave mediated long‐range interaction of breathers.